2014
DOI: 10.1210/jc.2014-1580
|View full text |Cite
|
Sign up to set email alerts
|

Teprotumumab, an IGF-1R Blocking Monoclonal Antibody Inhibits TSH and IGF-1 Action in Fibrocytes

Abstract: Teprotumumab attenuates the actions of both IGF-1 and TSH in fibrocytes. Specifically, it blocks the induction of proinflammatory cytokines by TSH. These results provide, at least in part, the molecular rationale for interrogating the therapeutic efficacy of this antibody in TAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 31 publications
7
121
0
3
Order By: Relevance
“…32 Some studies have shown their detection, 14,29-31 whereas others have not. 33,34 Given the evidence that actions of thyrotropin and thyroid-stimulating immunoglobulins are in part dependent on IGF-IR activity, 18,21 the clinical benefits reported here may result from attenuation of pathogenic signaling mediated through both IGF-IR and the thyrotropin receptor.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…32 Some studies have shown their detection, 14,29-31 whereas others have not. 33,34 Given the evidence that actions of thyrotropin and thyroid-stimulating immunoglobulins are in part dependent on IGF-IR activity, 18,21 the clinical benefits reported here may result from attenuation of pathogenic signaling mediated through both IGF-IR and the thyrotropin receptor.…”
Section: Discussionmentioning
confidence: 93%
“…18 In vitro studies of orbital fibroblasts and fibrocytes show that IGF-IR–inhibitory antibodies can attenuate the actions of IGF-I, thyrotropin, thyroid-stimulating immunoglobulins, and immunoglobulins isolated from patients with Graves’ disease. 18,21 These observations prompted a trial of teprotumumab, a fully human IGF-IR–inhibitory monoclonal antibody formerly known as R1507, 22 in patients with active, moderate-to-severe ophthalmopathy. In August 2016, after a review of the data from this trial, teprotumumab received a “breakthrough therapy” designation from the Food and Drug Administration.…”
mentioning
confidence: 99%
“…The IGF-1R was shown to be coexpressed with the TSHR on orbital fibroblasts and fibrocytes (88), and in vitro blocking of the IGF-1R attenuates TSH-dependent signaling (89). Serum IGF-1R autoantibodies have been detected only in subgroups of patients with GO (90) and do not seem to occur with significant prevalence in active GO.…”
Section: Targeting the Igf-1rmentioning
confidence: 99%
“…A recent study looked at fibrocyte expression of the TSH receptor and IGF-1 receptor in healthy donors and from patients with TED, and found that IGF-1R and TSH receptor are highly expressed in untreated TED fibrocytes. These fibrocytes were then treated with teprotumumab and were found to have lower levels of expression of IGF-1 receptor and TSH receptor, suggesting teprotumumab could have a role in reducing or even preventing TED [21].…”
Section: Key Pointsmentioning
confidence: 99%